2015
DOI: 10.1055/s-0034-1378734
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Uracil-, Coumarin- and Quinolone-Fused Benzosultams and Benzosultones

Abstract: An efficient method for the regioselective synthesis of uracil-, coumarin-and quinolone-fused benzosultams and benzosultones is reported. The method offers a synthetic route to highly functionalized sultam and sultone derivatives in 75-95% yield under mild conditions. Density functional theory studies have been used to explain the regioselectivity in the synthesis of the coumarin-and quinolone-fused sultams and sultones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The benzosultam, 4,7-dimethyl-3,4,7,8-tetrahydro-3λ 6 -[1,2]thiazino[4,3- f ]quinoline-3,3,8-trione ( 8l ) was synthesized from its precursor quinolone (6-amino-5-bromo quinolone derivative) with the reaction of 2-chloroethylsulfonyl chloride at 0 o C followed by Heck cyclization as described in our earlier report 20 . After synthesis of the compound 8l , the product was purified by column chromatography using silica gel (60–120 mesh size) as column matrix and eluted with 30% ethyl acetate–petroleum ether to afford the compound 8l as a white solid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benzosultam, 4,7-dimethyl-3,4,7,8-tetrahydro-3λ 6 -[1,2]thiazino[4,3- f ]quinoline-3,3,8-trione ( 8l ) was synthesized from its precursor quinolone (6-amino-5-bromo quinolone derivative) with the reaction of 2-chloroethylsulfonyl chloride at 0 o C followed by Heck cyclization as described in our earlier report 20 . After synthesis of the compound 8l , the product was purified by column chromatography using silica gel (60–120 mesh size) as column matrix and eluted with 30% ethyl acetate–petroleum ether to afford the compound 8l as a white solid.…”
Section: Methodsmentioning
confidence: 99%
“…coumarin and quinolone fused benzosultam, which may serve as a potential antifilarial drug. Based on this postulation, a series of twelve coumarin and quinolone fused benzosultams were synthesized 20 and tested for their efficacy in inducing mortality in the filarial parasite Setaria cervi as reported previously 21 . Amongst the tested compounds, a novel quinolone-fused cyclic sulfonamide (4,7-dimethyl-3,4,7,8-tetrahydro-3λ 6 -[1,2]thiazino[4,3- f ]quinoline-3,3,8-trione) was found to exhibit the highest efficacy with a low degree of toxicity on non-targeted cells and tissues 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the Z -bromoalkenes can be easily synthesized from the nucleophilic addition of N -alkyl- p -toluenesulfonamides to bromoacetylenes [ 50 ]. Later, Mondal and co-workers further applied this strategy into an intramolecular cyclization of aryl bromides for the regioselective formation of uracil-, coumarin-, and quinolone-fused benzosultams [ 51 ]. Using three equivalents of AgOAc as the efficient oxidant, in 2014, Laha et al demonstrated a Pd-promoted intramolecular oxidative coupling reaction of sulfonanilides, which offers a facile access to a range of biaryl sultams [ 52 ].…”
Section: Transition Metal-catalyzed Benzosultam Synthesismentioning
confidence: 99%
“…We have also applied Pd‐catalyzed intramolecular cyclization for the preparation of uracil‐, coumarin‐, and quinolone‐fused benzosultams 9.2a – h (Scheme ) . In this method regioselectivity in the cyclization step in the cases of the coumarin and quinolone substrates led predominantly to C‐5 cyclized products.…”
Section: Synthesis Of Sultamsmentioning
confidence: 99%